Stress analysis of drillstring threaded connections - Salihu, B. M. (Cranfield University, 2011)
The demand for energy from developed and developing economies of the world is driving the search for energy resources to more challenging environments. The exploration and exploitation of hydrocarbons now requires the drillbit to hit pay zones from drillships or platforms that are located on water surfaces below which is, possibly, in excess of ten thousand feet of water above the sea bed. From Brazil, to the Gulf of Mexico and the Gulf of Guinea on the western coast of Africa, hitherto unfamiliar, but now common, concepts in the drilling parlance such as ultra-deep drilling (UDD), ultraextended- reach drilling (uERD) and slimhole drilling, are employed to reach and produce reservoirs which a few decades ago would seem technologically impossible to produce. This is expected to exert tremendous demands on the physical and mechanical properties of the drillstring components. Limiting factors for reaching and producing oil and gas resources hidden very deep in the subsurface are both the capacity of the drilling rig to support the weight of the drillstring, which in some instances can be several kilometres long, and the bending, tensile and impact stresses the string has to withstand in well trajectories that are getting both longer and more tortuous. Associated with this increased well depths and complex well trajectories is the prohibitive cost penalty of a failed drillstring. The in-service failure of drillstrings has always been an issue in the industry long before the wells become this deep and complex. The global oil and gas industry estimates the cost of string failure to be in excess of quarter of a billion dollars annually. Researchers are continuously looking for ways to design against string failure and improve the level of confidence in drillstrings. Defect-tolerant design, tooljoint geometry modification and surface coldworking are just a few of the ideas that have gained mileage in this effort. Others that are now in consideration are the use of nonconventional materials such as aluminium and titanium alloys for drillstring components. More novel, still, is the use of a combination of two materials - one ‘softer’ than the other to form a hybrid string of two materials of unequal moduli of elasticity. This is done to make the string lighter, reduce stress concentration factor at the connections and place fatigue resistant materials in areas of high well bore curvature.In this work a computational technique in the form of two-dimensional finite element analysis is used to develop a robust model of a drillstring connection and to analyse the stresses on the model of a threaded connection of standard drillstring tooljoint made from alloy steel. Further comparative analyses were undertaken on models of drillstrings made from a newly developed drillstring material for ultra-deep drilling, the UD-165, aluminium and titanium alloys and, finally, on hybrid drillstrings made from two different materials of unequal moduli of elasticity. The aim is not only to develop and validate a better method of computational drillstring analysis but also to use the model to investigate and suggest areas of optimisation that will benefit industry especially in the areas hybrid strings.
Keywords: Hybrid Strings; Computational Mechanics; Fatigue; Ultra-Deep Drilling; Extended-Reach Drilling; Unconventional Drillstrings; Aluminium Drillstrings; Titanium Drillstrings